Policy Option for Agriculuture in Facing The Impact of Sea Level Rise in The South Kalimantan Province - R. Saidy, Akhmad; Azis, Yusuf (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 10, No. 1 Februari 2010, 2010)
-